Physical development of young 11-13-year-old swimmers and divers - Raspopova, E. A.; Chebotareva, I. V. (The Russian Journal of Physical Education and Sport, 2019)
Morphofunctional indices mainly determine the propensity of athletes for different kinds of sport and can fulfill the role of the restrictor in high sports results achievement. Athletes` morphofunctional indices study in different specializations is one of the most important directions of sports science. In recent years a lot of material is gathered concerning the dynamics of athletes` physical and biological development. The connection with the tempo of sports achievements increase is shown. However, constitution and physical development indices comparison among young swimmers and divers wasn`t held earlier. Materials. The article compares morphofunctional indices of young 11-13-year-old swimmers and divers, showed the differences in physical development of swimmers and divers from sports school of the Olympic reserve in Moscow. Research methods. Anthropometry, weight fractionation, experimental statistics. Results. We revealed the differences in physical development and weight content of 11-13-year-old divers and swimmers. So, the swimmers have higher indices of body length and mass, chest circumference, divers have the advantage of an active body mass. Conclusion. The held research in water since the age of 11. These differences are, apparently, conditioned by sports selection influence, on the one hand, and the process of sports training on the other.